(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The first aim of this research is to show if the integration of different digital resources in learning in the scope of the university contribute to improve in quality the educational-learning process in terms of utility, frequency of use and student motivation. Specifically, it is analyzed the digital resources such as YouTube, Skype, Twitter, instant messaging, using apps, web pages, software, virtual platforms, blogs, wikis, iPad, interactive whiteboards, video games, television and radio for teaching-learning. Furthermore, it is find out if exist different types of students with respect to their evaluations in utility and use of each resource. It is made a correlational study through an ad-hoc survey to 13 Spanish Universities. The results show that there are four dimensions of digital resources that have significant influences in the motivation of the university student to learn. The students are sorted out in two types, significantly differentiated, called «technologists» and «technophobes».